Extended photoperiod improves growth and nutritional quality of pak choi under constant daily light integral - Susilo, Kartika R.; Eu, Anastasia; Besemer, Britt; Heuvelink, Ep; de Vos, Ric C. H.; Marcelis, Leo F. M. (Frontiers in Plant Science, 2025)
Introduction and AimThe duration of light exposure each day, termed the photoperiod, is a crucial environmental cue that influence several aspects of plant physiology, including growth, development, and metabolic activity. Adjusting the photoperiod in controlled agriculture systems has the potential to improve crop yield and nutritional content. However, the benefits of longer photoperiods compared to higher light intensities under a fixed daily light integral (DLI) have not been thoroughly examined for many leafy vegetables. DLI is the total amount of light a plant receives per day and it is the product of photoperiod and light intensity. This study aimed to determine to what extent the effect of DLI on pak choi (Brassica rapa L. subsp. chinensis) growth, yield and quality depends on whether DLI is changed by light intensity (PPFD) or by photoperiod.MethodsThree cultivars (‘Hybrid Special’, ‘Red Summer’, and ‘Shanghai Green’) were grown under four different DLIs (10.8, 13.5, 16.2, and 18.9 mol m-2 d-1). These DLIs were achieved either by varying the photoperiod (12, 15, 18 and 21 hours) at a constant PPFD 250 µmol m-2 s-1 or by varying the PPFD (167, 208, 250, and 292 µmol m-2 s-1) at a constant photoperiod (18 hours). ResultsIncreasing DLI by extending the photoperiod resulted in more growth than increasing DLI by increasing PPFD. Photoperiod extension also generally resulted in higher light use efficiency and energy use efficiency than increasing DLI by increasing PPFD. The content of vitamin C, glucosinolates and many other metabolites increased significantly with higher DLI regardless whether DLI was increased through PPFD or photoperiod. However, DLI did not affect shelf life and overall visual quality.DiscussionThese results suggest that extending photoperiod is a more effective strategy than increasing light intensity for optimizing leafy vegetable production in controlled environments.